2023
DOI: 10.30621/jbachs.1092493
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Healthy Lifestyle Behaviors and Physical Activity Levels of Elderly İndividuals Residing in the City Center and Rural, and Analyzing Their Relationship with Depression

Abstract: Purpose: Our study aimed to determine the differences in the levels of physical activity and healthy lifestyle behaviours in elderly individuals living in urban and rural and to examine their relationship with depression. Methods: Individuals who are over 65 and residing in the city and rural were included in the study. The Healthy Lifestyle Behaviour’s Scale-II, the Physical Activity Scale for the Elderly, and the Geriatric Depression Scale-15 were used on the participants &#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our findings contribute to this field by showing that rural older adults maintain PA guidelines despite intensive TV viewing, possibly due to a rural lifestyle that allows for a more active life compared to urban settings (Köroğlu et al, 2023). The well-established association between reduced PA and increased risk of depression emphasizes the therapeutic potential of structured PA in mood disorders (Hallgren et al, 2020a).…”
Section: Sedentary Behavior and Depressive Symptomsmentioning
confidence: 64%
See 1 more Smart Citation
“…Our findings contribute to this field by showing that rural older adults maintain PA guidelines despite intensive TV viewing, possibly due to a rural lifestyle that allows for a more active life compared to urban settings (Köroğlu et al, 2023). The well-established association between reduced PA and increased risk of depression emphasizes the therapeutic potential of structured PA in mood disorders (Hallgren et al, 2020a).…”
Section: Sedentary Behavior and Depressive Symptomsmentioning
confidence: 64%
“…The rural setting of our study, which provides different motivations and opportunities for PA (Köroğlu et al, 2023), may also have attenuated the effect of PA on DS.…”
Section: Physical Activity and Depressive Symptomsmentioning
confidence: 99%
“…Studies have revealed that physical activity through exercise has been shown to have a tremendous positive impact on the health of older adults (Cheng et al, 2013). In various scientific studies, regular exercise has been shown to improve quality of life, reduce the risk of various chronic diseases, and support physical independence (Galle et al, 2023;Köroğlu et al, 2023). However, many older adults are less aware of these benefits, and they may view exercise as something difficult to do at their age.…”
Section: Introductionmentioning
confidence: 99%